Human resource strategy formulation, implementation, and impact - Bamberger, Peter; Meshoulam, Ilan.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
'Human Resource Strategy' reviews 20 years' worth of empirical and theoretical research, presenting it in the context of the critical strategic decisions that executives must make.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Personnel management; Electronic books